UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SELF CONTROL SISWA DI SMA NEGERI 3 BEKASI - Rika Komala; Akmal Rizki Gunawan (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
This research is motivated by deviant behavior carried out by teenagers, especially students such as brawls, free sex, drug abuse, bullying, drunkenness, and so on. Most of the causes of this event is encouragement from peers. The purpose of this study was to determine the efforts of sIslamic Religious Education Teachers in increasing student self-control at SMA Negeri 3 Bekasi. With a qualitative descriptive method, this study tries to explore the extent to which a teacher can develop student self-control. The data collection techniques used were observation, interviews with Islamic Religious Education Teachers and documentation studies. The results showed that the teacher's efforts to improve student self-control were being uswah hasanah, making habituation, implementing joint supervision and mentoring policies and increasing discipline.